Unclassified Diffuse Ductal Cholangiocarcinoma; Report of a Case. (4th March 2014) - Aydın, Ünal; Özsan, İsmail; Karabuğa, Türker; Alpdoğan, Özcan; Ortaç, Ragıp; Yoldaş, Ömer; Şahin, Erkan
Abstract : Cholangiocarcinoma (CCA) is the second most common malignant tumor of the liver. It is simply classified as intrahepatic and extrahepatic CCA (including perihilar and distal extra hepatic CCA) according to the anatomic localization. Various classification systems were described for staging cholangiocarcinoma. We represent an interesting case of cholangiocarcinoma which is in the shadow area of classification by involving intrahepatic, hilar, and distal extra hepatic bile ducts. To our knowledge, this is the first case in the literature with diffuse bile duct involvement.